Differential Potentiation of Retinoic Acid Effects against Human Breast Cancer Cells by Unsaturated Fatty Acids. (3rd October 2018) - Quiroga, Patricia L.; Soria, Elio A.; Valentich, Mirta A.; Eynard, Aldo R.
Abstract: Retinoic acid (RA) and unsaturated fatty acids (UFA) are proposed as nutritional anticancer agents. Nonetheless, the activity of their combination on human breast cancer needs further study. Our aim was to evaluate this activity on the MCF-7 and ZR-75-1 cell lines treated with 1 µM RA and 50 µM of γ-linoleic (GLA, ω-6), eicosapentaenoic (EPA, ω-3), oleic (OA, ω-9), or eicosatrienoic (ETA, ω-9) acids. The following cellular responses were compared by ANOVA and Fisher test ( P < 0.05): fatty acids, E-cadherin, actin (differentiation), conjugated dienes, γ-glutamyltranspeptidase activity (stress), and viability, which were correlated by partial least squares regression. Although both cell lines responded differentially, RA modified unsaturated fatty acids, increased differentiation, reduced γ-glutamyltranspeptidase, and viability. RA differentiating activity on ZR-75-1 was morphologically enhanced by UFA. Stress induction with γ-glutamyltranspeptidase decrease and conjugated dienes was promoted by ETA in MCF-7, and EPA and OA in ZR-75-1. RA-related reduced viability was potentiated by EPA and OA in both lines. GLA was less active. Therefore, unsaturated fatty acids (ω-3/ω-9) potentiated the multitarget retinoic acid activity against these human breast cancer cells.